Lycopenoids: Are lycopene metabolites bioactive? - Lindshield, Brian L.; Canene-Adams, Kirstie; Erdman, John W. Jr. (My University, 2008)
In vitro lycopene is the most potent antioxidant among carotenoids. While antioxidant function may be relevant to health, we hypothesize that metabolites of lycopene may be bioactive and responsible for the beneficial effects of tomato product consumption. We term these metabolites "lycopenoids," which we believe may be produced from carotenoid monooxygenase (CMO) II, paralleling the production of retinoids from [beta]-carotene by CMO I. We present evidence suggesting that tomato carotenoid metabolites may be responsible for the reduced risk of prostate cancer seen in men consuming high levels of tomato products. Finally, we identify gaps in knowledge in this evolving area of carotenoid research.
Keywords: Lycopenoids; Lycopene; Prostate cancer; Carotenoids; Tomato; Carotenoid monooxygenase; CMO; Beta-carotene; Phytoene; Phytofluene